THERMAL AND TECHNOLOGICAL PECUHARITIES OF PRODUCTION OF LARGE CASTINGS OF ALUMINUIM ALLOYS INTO CONSTANT FORM - A. P. Melnikov; M. A. Sadoha; N. E. Bondarik; B. A. Krajev; B. V. Kurakevich (Литьë и металлургия)
The heat scheme of the chill mold temperature equalization, what is especially important at automation of the chill machines working is offered.